Polar bears [book with audioplayer] - Koestler-Grack, Rachel A., 1973- (Blastoff! readers. Animals at risk., 2022)
"Simple text and full-color photography introduce beginning readers to the threats to and protections for polar bears. Developed by literacy experts for students in kindergarten through third grade" --Provided by publisher.